The in vivo hydrocarbon formation by vanadium nitrogenase follows a secondary metabolic pathway - Johannes G. Rebelein (Nature Portfolio, 2016)
Nitrogenases reduce inorganic nitrogen to organic ammonia in a crucial step of the nitrogen cycle. Here the authors show that the vanadium-nitrogenase ofAzotobacter vinelandii can also catalyse the in vivoconversion of carbon monoxide to hydrocarbons in a secondary non-biosynthetic pathway.